Pengaruh Literasi Keuangan Terhadap Pola Konsumsi Petani Jagung di Kabupaten Sumenep - Agustin, Puteri Nanda Nuriyantika; Wijayanti, Dian Eswin; Priyanto, Moh. Wahyudi (Journal of Agribusiness Science and Rural Development, 2023)
A low level of financial literacy can encourage consumptive behavior, so education regarding financial literacy is needed to suppress this consumptive behavior. The aim of the research is to find out the influence of financial literacy on the consumption patterns of corn farmers in Sumenep Regency. The method used is quantitative with multiple linear regression analysis tools. The research was conducted with a sample of 80 farmers in Sumenep Regency. Data collection was carried out directly with a questionnaire so that the data used was primary data. The research results show that financial literacy has an influence on the consumption patterns of corn farmers, but there needs to be efforts to increase financial literacy so that farmers understand better managing their finances so that farmers' consumption patterns become better. This research has implications for improving farmers' welfare in managing finances and good consumption patterns. Apart from being useful for farmers, this research is also useful for students as a reference in carrying out assignments and researchers who want to carry out related research.